2007
DOI: 10.1111/j.1365-2621.2006.01256.x
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional quality of African catfish Clarias gariepinus (Burchell 1822): a positive criterion for the future development of the European production of Siluroidei

Abstract: The aims of this study were to evaluate the nutritional quality (proximate composition, amino and fatty acid profiles, cholesterol and mineral contents) of African catfish (Clarias gariepinus) and determine the effect of different cooking methods (grilling, boiling and frying) on biochemical composition. Frying produced the highest water loss and fat gain (P < 0.05). Frying also affected the fatty acid composition significantly (P < 0.05), increasing oleic (18:1n-9) and linoleic (18:2n-6) acid contents. The ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

31
72
4
13

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 71 publications
(120 citation statements)
references
References 46 publications
31
72
4
13
Order By: Relevance
“…The Na content of trout, ranging from 380 to 3200 mg/kg DM was reported by Wheaton and Lawson (1985) and 335-607 mg/kg by Gokoglu et al (2004). A similar finding was reported by Rosa et al (2007) indicating significantly increased Na content in fried and grilling African catfish. The K content of raw fish was found to be 2195 mg/kg DM.…”
Section: Resultssupporting
confidence: 76%
See 2 more Smart Citations
“…The Na content of trout, ranging from 380 to 3200 mg/kg DM was reported by Wheaton and Lawson (1985) and 335-607 mg/kg by Gokoglu et al (2004). A similar finding was reported by Rosa et al (2007) indicating significantly increased Na content in fried and grilling African catfish. The K content of raw fish was found to be 2195 mg/kg DM.…”
Section: Resultssupporting
confidence: 76%
“…The Ca content of raw fish was found to be 290 mg/kg DM. This value is higher than that reported by Rosa et al (2007); Ersoy and Ozeren (2009) in African catfish and lower than that reported by Gokoglu et al (2004) in rainbow trout. No significant difference of Ca content was noticed in all the cooking methods (p>0.05).…”
Section: Resultscontrasting
confidence: 54%
See 1 more Smart Citation
“…Water loss, occurring during the production of fish powder, resulted in higher protein content. Similarly, after cooking, a significant water loss was reported by Weber, Bochi, Ribeiro, Victorio, and Emanuelli (2008) in silver catfish; Rosa, Bandarra, and Nunes (2007) and Ersoy and Ozeren (2009) in African catfish.…”
Section: Resultsmentioning
confidence: 57%
“…Saguy and Dana (2003) reported that the increase in fat content can be attributed to the oil penetration on the fish fillet after water is partially lost by evaporation during cooking. In addition, similar results have been reported for African catfish (Rosa et al., 2007) and rainbow trout (Gokoglu, Yerlikaya, & Cengiz, 2004) fried in vegetable oils.…”
Section: Resultsmentioning
confidence: 99%